Pengaruh Metode Team Quiz terhadap Motivasi Belajar Siswa pada Pembelajaran Matematika - Kanarasi, Yabes Maxrobin; Lefrida, Rita; Alfisyahra, Alfisyahra; Pathuddin, Pathuddin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to examine the effect of the Team Quiz method on student learning motivation in mathematics subjects in class VIII SMP Negeri 2 Poso Pesisir Utara. This research design uses a quasiexperiment method consisting of two groups, namely the experimental class and the control class. The experimental class was class VIII B consisting of 26 students and the control class was class VIII A consisting of 28 students. Data were collected through a learning motivation questionnaire consisting of 30 statement items, which were used as pretest and posttest questionnaires in the Experimental class and posttest questionnaires in the control class. Data analysis was carried out using descriptive and non-parametric statistical techniques, specifically the Mann-Whitney test as hypothesis data analysis. Hypothesis testing using the Mann-Whitney test showed a significance value (Asymp. Sig. 2-tailed) of 0.000, which is smaller than 0.05. This indicates a significant difference in student learning motivation before and after the application of the Team Quiz method. Thus, it can be concluded that the Team Quiz method has an effect in increasing student learning motivation in mathematics learning in class VIII SMP Negeri 2 Poso Pesisir Utara. Keywords: Team Quiz Method, Learning Motivation, Math Learning